Mayors on the global stage – a political star is born - Pinault, Emmanuelle; Hansen, Simon (Økonomi & Politik, 2026)
It may sound counterintuitive that mayors from some of the largest cities in the world spend time participating in and contributing to international cooperation on climate challenges. After all, they are primarily accountable to their local electorate. However, the fact is that a global city network such as C40 offers these mayors resources such as new ideas, a closely knit, exclusive and confidential community of peers, and some very concrete solutions that can be directly implemented in order to meet some of the acute climate challenges in the large cities. In this way, cities and their global networks contribute to filling the governance void that states have created in the area of climate change.